Cometography : a catalog of comets. - Kronk, Gary W. (Cambridge University Press, 2009)
Cometography is a multi-volume catalog of every comet observed throughout history. It uses the most reliable orbits known to determine the distances from the Earth and Sun at the time a comet was discovered and last observed, as well as the largest and smallest angular distance to the Sun, most northerly and southerly declination, closest distance to the Earth, and other details to enable the reader to understand the physical appearance of each well-observed comet. Volume 4 provides a complete discussion of each comet seen from 1933 to 1959. It includes physical descriptions made throughout each comet's apparition. The comets are listed in chronological order, and each listing includes complete references to publications relating to the comet. This book is the most complete and comprehensive collection of comet data available, and provides amateur and professional astronomers, and historians of science, with a definitive reference on comets through the ages.